259 Healthcare system affecting systemic lupus erythematosus in asia-pacific countries. (April 2019) - Choi, Chan-Bum; Oon, Shereen; Nikpour, Mandana; Bae, Sang-Cheol
Abstract : Background: There are between-country disparities in healthcare systems in Asia and Pacific region. The aim of the study was to construct profiles of disparities in healthcare system affecting systemic lupus erythematosus (SLE) in Asia and Pacific countries. Methods: An online survey was conducted between March and October 2018 of rheumatologists specializing in SLE in the Asia and Pacific region. Responses were collected anonymously and analyzed, using descriptive statistics Results: The survey was sent to 45 SLE rheumatologists and 20 (44.4%) provided a complete response. Responders were from 14 countries in the Asia-Pacific region. (Australia, Bangladesh, China, Hong Kong, Indonesia, Japan, Republic of Korea, Kuwait, Myanmar, New Zealand, Philippines, Singapore, Taiwan, Thailand). The estimated prevalence of SLE was 51.1 per 1 00 000 (IQR 26.5 76.9) with 50% (IQR 36.7 60.0) having lupus nephritis. Most respondents (66.7%) reported that 80% to 100% of the general population had public health insurance. Fifty percent felt that their countrys health care system functions quite well on the whole, and there are only a few changes necessary to make it function even better. And another 50% felt that it functions quite well on the whole, and there are only a few changes necessary to make it function even better. Assessment using a validated disease activity measure for SLE was regularly performed by 66.7% of the respondents and they all used Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) with 2 responders using both SLEDAI and British Isles Lupus Activity Group (BILAG). Eighty-eight percent responded that mycophenolate mofetil (MMF) was approved for treatment of SLE in their country with 72.2% responding that it was reimbursed. It was 83.3% and 94.4% for intravenous (IV) cyclophosphamide, 50.0% and 80.0% for tacrolimus, 72.2% and 5.6% for belimumab and 33.3% and 33.3% for rituximab, respectively. MMF was most commonly used in induction therapy for lupus nephritis (40.0%, IQR 25.0 65.0), followed by IV cyclophosphamide National Institute of Health (NIH) protocol (20.0%, IQR 4.0 40.0), IV cyclophosphamide Euro-Lupus Nephritis Trial protocol (15.0%, IQR 5.0 27.5), tacrolimus plus MMF (2.5%, IQR 0.0 8.8), tacrolimus (0.0%, IQR 0.0 5.0), and oral cyclophosphamide (0.0%, IQR 0.0 2.0). Conclusions: There are disparities influencing the management of SLE in Asia and Pacific countries. Some of the recommended treatments for SLE are not approved and not reimbursed for management of SLE in some Asia and Pacific countries. Funding Source(s): None